Analysis Of Marketing Strategy At Business Resources Store Bintuhan Kaur Regency - Dezandra Afiro; Sulisti Afriani; Yanto Effendi (Penerbit Jurnal Indonesia, 2021)
Marketing strategy is a form of plan that unravels in the marketing field. To obtain optimal results, this marketing strategy has a broad scope in the field of marketing, including strategies dealing with competition, pricing strategies, product strategies, service strategies and so on. The aim of this research is to determine the marketing strategy at Toko Sumber Bisnis Bintuhan, Kaur Regency. The sample in this study were 30 people consisting of 4 employees at Toko Sumber Bisnis Bintuhan, Kaur Regency for internal factors and 26 people for external factors, namely customers. The analysis method used was SWOT analysis consisting of the Internal Strategy Factor Matrix (IFAS) and the External Strategy Factor Matrix (EFAS). The results showed that the marketing strategy at Toko Sumber Bisnis Bintuhan of Kaur Regency supports the aggressive strategy, or SO strategy in SWOT matrix. The result of the sum of the strengths owned is 43.20 while the weaknesses are 26.90, then the internal quadrant of the factors is 43.20 - 26.90 =16.30 which means the ability of Toko Sumber Bisnis Bintuhan of Kaur Regency to utilize the strengths and minimize the weaknesses that exist on the internal. The chances of this strategy are 42.60 and the threat is 23.41. So the external quadrant factors are 42.60 - 23.41 = 19.19, which means that the high ability of Toko Sumber Bisnis Bintuhan of Kaur Regency to take advantage of opportunities and overcome the threats faced by companies in marketing clothes, bags and shoes.